Tanggung Jawab Hukum Penjual terhadap Barang yang Rusak dalam Transaksi Jual Beli Online - Cicilia Presy Kolantung; Wenly R. J. Lolong; Merry Lenda Kumajas (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of digital technology has driven the rapid growth of online buying and selling transactions. However, this phenomenon also increases risks for consumers, particularly regarding the receipt of damaged goods or goods that do not meet promised specifications. This study aims to analyze sellers' legal liability for damaged goods in online buying and selling transactions under the Indonesian Consumer Protection Law. Under applicable regulations, sellers are obligated to provide compensation, restitution, or return goods if a product defect is proven to be not due to consumer negligence. The principles of prudence and transparency in digital transactions are crucial aspects that businesses must adhere to to maintain consumer trust and prevent detrimental trade practices. Furthermore, this study also discusses the procedures for returning damaged goods in online buying and selling transactions in Indonesia. Applicable laws regulate complaint and dispute resolution mechanisms that allow consumers to claim their rights, either through consumer dispute resolution channels or through litigation, if necessary. Challenges frequently faced by consumers include unclear return policies, additional shipping costs, and long turnaround times. Therefore, there is a need for strengthened regulations and stricter oversight of e-commerce platforms to ensure effective legal protection for consumers.